Competences needed for the university faculty in view of pedagogy students - Baranova, Sanita; Kaļķe, Baiba (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Diverse evaluation of the study process and the activities of all participants involved in it is a significant element in the context of introducing quality culture at the higher education institutions (HEI). It is a common practice in HEI to carry out students’ surveys in order to receive students’ evaluation on the quality of the study process as such, the study curriculum, the content and organization of particular subjects. On the basis of the performed analysis of the scientific and didactic literature, the article describes students’ survey and the possibilities of applying its results in assessing the quality of the university faculty’s professional activities. The survey of pedagogy students was performed in the empirical study which helped to find out students’ understanding about the competences needed for the university faculty in their professional activities in the study process at higher education institution and the professional development needs of the university faculty in view of pedagogy students are defined.